Using new technologies for improving psychotropic medication adherence - Iniatis, Giorgos; Georgiou, Giorgos; Kassianos, Angelos P.; Nicolaou, Silouanos; Papaconstantinou, Electra (My University, 2016)
Background: Approximately one out of two patients do not take their medication three months after therapy starts; while in patients with mental disorders this number varies. The WHO published a guide for clinicians, advising them to develop strategies for improving medication adherence. Aims: The aim of this project is to develop a smartphone application that will help patients adhere to their psychotropic medication and clinicians to keep track of their patients’ adherence. Methods: In Phase I we will design an application based on scientific evidence and employ software and psychological (i.e. cognitive behavioural therapy) techniques to inform the applications’ features. In Phase II we will use patient and clinical focus groups to validate in the process the applications’ usability and effectiveness. Results: We expect to develop a framework to assess the feasibility and usability of the application’s features. We also expect to have a first version of the application, which will be used in further studies using evaluation methodologies to update its content. Project is in the early stages of development. Conclusions: Implementing such an app will lead to an effective and possibly low cost method for improving psychotropic medication adherence with significant benefits for both patients and clinicians. The applications’ integration with usual care will lead to social Benefits like higher quality of care, clinical effectiveness, reduced healthcare costs and time consumption, advantages of online possibilities and better patient outcomes like quality of life and patient satisfaction with care provision.
Keywords: Medication Adherence; mHealth; Smartphone application; Psychotropic Drugs; Compliance; New technologies; Health Psychology; Doctor-patient communication; Mobile application development; Pharmacy